If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -33 = -3(1 + -4x) Reorder the terms: -33 + 7x = -3(1 + -4x) -33 + 7x = (1 * -3 + -4x * -3) -33 + 7x = (-3 + 12x) Solving -33 + 7x = -3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -33 + 7x + -12x = -3 + 12x + -12x Combine like terms: 7x + -12x = -5x -33 + -5x = -3 + 12x + -12x Combine like terms: 12x + -12x = 0 -33 + -5x = -3 + 0 -33 + -5x = -3 Add '33' to each side of the equation. -33 + 33 + -5x = -3 + 33 Combine like terms: -33 + 33 = 0 0 + -5x = -3 + 33 -5x = -3 + 33 Combine like terms: -3 + 33 = 30 -5x = 30 Divide each side by '-5'. x = -6 Simplifying x = -6
| (x+3)(x-1)(x-1)=0 | | 4x+10=3y | | r=n+3.5 | | 8x^3-27x=0 | | -7(3x+4)-12x-8= | | 7+54= | | -4r-(-6r+9)= | | Y+7(3)=9 | | 119+g=328 | | (5x+2)+(8x+4)=15x-18 | | -4x+3x-3=-x-3 | | 7.4+44.4=3.2a+86.4 | | -3x+2x+3=16 | | -6y+13+2y=-15 | | 2(x+2)=-16 | | 2t-3(t-2)=t+6 | | x+x+8-5-3=22 | | -0.7z=-21 | | -9z-9z=-z+2-4z | | 9x-3x+102=9x+36 | | 4y-19=2x-14 | | -54.4=-6 | | 9(7-3y)+3y=39 | | X^4-6x^2+9x^2=0 | | y=2x^2-14x+26 | | 6-(2x-3)=3-3x | | 3(2x-7)+4x=-4-(2x-7) | | t+19=19 | | X^2-4x-4y+8=0 | | a+8-5a=-a-15a+11a | | 19x-6=15x-18 | | 28-5x=-4x |